"Real" bodies in plus-size fashion. Issue 3 (2nd September 2022) - Czerniawski, Amanda M.
ABSTRACT: In recent years, a number of clothing brands have launched viral body-positive marketing campaigns featuring diverse groups of women of various sizes and body types in Photoshop-free ads. These anti-Photoshop campaigns that stress "real" bodies "exactly as they are" serve to counter the narrow and quite distorted image of beauty presented by Hollywood and Madison Avenue. While these campaigns alter the landscape by eliminating Photoshop from their image production process, their attempt to increase size diversity actually maintains the status quo since the plus-size models on display are typical commercial plus-size fashion models who are on the smaller end of the plus-size spectrum. Despite its best efforts, fashion hides bodies over a size 16 from consumers. In this paper, I discuss the regulation of plus-size models and the strategic use of padding in fashion, and how this perpetuates a narrow and fabricated image of beauty. I also discuss the rise of size 22 model Tess Holliday, who revolutionizes the commercial definition of plus size and rages against the status quo in fashion.